Expressed and unexpressed social needs in low‐income adults in the U.S. (30th December 2020) - Verdecias, Niko; Garg, Rachel; Steensma, Joe; McQueen, Amy; Greer, Regina; Kreuter, Matthew W.
Abstract: Many healthcare organisations are now routinely screening patients for social needs such as food and housing. It is largely unknown whether the needs they identify would have been expressed by the patient in the absence of screening. To better understand expressed and unexpressed social needs, we administered a social needs screener to 1, 397 low‐income adults who called a 2‐1‐1 helpline in Missouri seeking assistance with social needs between June 2017 and October 2019. Merging data from the screener and 2‐1‐1, we found that the screener identified all of the social needs expressed to 2‐1‐1 for about half the participants, and on average identified at least one social need not expressed to 2‐1‐1 (i.e., unexpressed needs). Certain social needs (utility payment assistance, housing) were much more likely to be expressed than unexpressed, while others (childcare, employment, personal safety) were almost universally unexpressed. In regression analyses, having certain expressed needs significantly increased the odds of having certain unexpressed needs. For example, those seeking transportation assistance from 2‐1‐1 had greater odds of unexpressed needs for food (OR = 3.19; 95% CI = 1.45–7.02) and healthcare (OR = 2.18; 95% CI = 1.06–4.48) than those not expressing transportation needs. Those seeking employment assistance from 2‐1‐1 had greater odds of unexpressed needs for personal safety (OR = 3.04; 95% CI = 1.20–7.68) and healthcare (OR = 2.58; 95% CI = 1.15–5.77) than those not expressing employment needs. Implications for healthcare (screening detects expressed and unexpressed needs) and social service organisations (certain requests may be markers for other needs) are discussed.